Rancang Bangun Pengaturan Bukaan Choke pada Genset Hybrid (Bensin dan Bioetanol) - Ridwan Baharta; Bastaman Syah (Jurusan Teknologi Pertanian, 2014)
Until recently, generator available in the market, generally gasoline or LPG. Conversion of gasoline to fuel bio-ethanol requires some adjustments.The research conducted was a further development of research Nurjan Didik Purwanto in 2011. The research was focused on adjustment of airand fuel ratio after the fuel in the generator set was replaced with bioethanol. Bioethanol has a higher octane rating than gasoline, but it has a lower calorific value than petrol. With this condition, it is necessary to attempt to increase the ratio of air and fuel to be more